STUDI PERBAIKAN FAKTOR DAYA BEBAN INDUKTIF DENGAN KOMPENSATOR REAKTIF SERI MENGGUNAKAN SAKELAR PEMULIH ENERGI MAGNETIK - , FAUZAN, ST, Dr. Eng. F. Danang Wijaya, S.T., M.T,. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nowdays, most of electric loads character in industry is inductive which definetly has low power factor and caused inductive reactance raises. This inductive reactance need to be compansated using apropriate equipments. One of them is the Magnetic Energy Recovery Switch (MERS) which to set capacitor charging and discharging time by controlling firing angle shift of mosfet gate in MERS circuit. MERS is installed between voltage source and single phase induction motor as the load so it controls voltage to the load. As an equipment that gives correction to power factor, MERS also effect terminal voltage on induction motor that lead to changes in rotation speed of motor. Capacitor reactance is high when capacitance is low, and MERS reactance is small when firing angle of mosfet gate is big. When the capacitor reactance is bigger than MERS reactance then capacitor voltage has discontinue waveform, when they are equal then its waveform is balance, and when capacitor reactance is smaller than MERS reactance then its waveform is dc-offset. This study results that MERS is able to correct power factor up to 0.898 with load voltage 244.6 volts using C = 2.2 ÂµF at firing angle of 1600 and lead to changes of voltage terminal of inductive load.